治疗丝聚蛋白相关湿疹和哮喘的药物成本增加. (17th September 2018) - Soares, P.; Fidler, K.; Felton, J.; Tavendale, R.; Hövels, A.; Bremner, S.A.; Palmer, C.N.A.; Mukhopadhyay, S.
Abstract : Linked Article: Soares et al. Br J Dermatol 2018;179 :717–723